Pelatihan Peningkatan Kapasitas Manajemen Organisasi dan Olahraga Pada Cabang Olahraga di Koni Kabupaten Mojokerto - Agung Prabowo, Suryanto; Luthfi Abdil Khuddus; Eva Ferdita Yuhantini; Hapsari Shinta Citra Puspita Dewi; Erta; Nurshalsabila Rhesa Pandhadha Putra; Hijrin Fithroni; Alvin Afandi (Laksana Olahraga, 2025)
Abstract: In response to the low managerial capacity of sports branch management, especially in terms of leadership, administration, and systematic coaching of athletes' achievements. Training on Capacity Building of Organizational and Sports Management was held at KONI Mojokerto Regency. Preliminary results suggest that many administrators lack sufficient managerial experience, leading to poorly managed sports organizations. The target of this training is the sports that will win medals at the 2023 Porprov. The training is designed in five stages, including field observation, coordination, an online focus on identifying problems and solutions, the implementation of training, and evaluation of the activity's results. Performance coaching management (including talent identification), organizational leadership, and administration and reporting are the main topics of training. The results of the pre-test and post-test showed a significant increase in the aspects of understanding the organization's goals, the benefits and functions of sports, program planning, athlete identification, and report preparation. The difference in scores before and after training was significantly demonstrated by the effectiveness of the training intervention. The evaluation of the quality of training implementation from the aspects of material, organizers, facilities, speakers' abilities, and the absorption of participants was, on average, in the category of "very good" (≥90%). In addition, follow-up from participants showed that most were able to implement the training results in organizational activities, both individually, in clubs, and their respective sports organizations. Documentation of activities in the form of publications in online mass media and YouTube videos also strengthens the transparency and replication of the program. This training not only improves the competence of participants but also becomes a strategic model for the sustainable development of regional sports institutional capacity.